Hubungan Antara Prilaku Masyarakat Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Rawat Inap, Kecamatan Bumi Waras, Kota Bandar Lampung Tahun 2022 - Indriyogi, Sophie Kirana; Murwanto, Bambang; Helmy, Helina; Usman, Sarip (Universitas Malahayati Bandar Lampung, 2023)
Background: Pulmonary tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis and is still a world health problem, including Indonesia and Indonesia ranks third after India and China.Various risk factors that cause pulmonary tuberculosis are age, gender, education level, occupation, smoking habits, bedroom occupancy density, lighting, ventilation, house conditions, air humidity, nutritional status, socioeconomic conditions and behavior, which environmental factors play a major role.Purpose: The purpose of this study was to determine the relationship between community behavior and the incidence of pulmonary tuberculosis in the working area of the Sukaraja Inpatient Public Health Center, Bumi Waras District, Bandar Lampung City in 2022.Methods: This type of research includes analytical research with a case control design. The case population of this study were patients with pulmonary tuberculosis recorded in medical records at the Sukaraja Inpatient Health Center as many as 119 people, while the control population in this study were non-pulmonary tuberculosis sufferers who resided in the working area of the Sukaraja Inpatient Health Center. The case sample in this study was 47 people who were recorded in the Tuberculosis case report in the Sukaaja Inpatient Health Center work area and the control sample in this study was 47 people or people who were not recorded as suffering from or had suffered from Pulmonary Tuberculosis who resided in the work area of the Inpatient Health Center Sukaraja. Results: The results of the bivariate analysis showed that the value of p = 0.123 > = 0.05 then there was no relationship between knowledge and the incidence of pulmonary tuberculosis in the working area of the Sukaraja Inpatient Health Center in 2022, p value = 0.023 < = 0.05 then there was a relationship between attitude and the incidence of pulmonary tuberculosis in the working area of the Sukaraja Inpatient Public Health Center in 2022 and the value of p = 0.023 < = 0.05, then there is a relationship between the action and the incidence of pulmonary tuberculosis in the working area of the Sukaraja Inpatient Health Center in 2022. Conclusion: In future research to determine the relationship between factors and the incidence of pulmonary tuberculosis more specifically, it is necessary to carry out further research with a better method design.Suggestion: for Community Health Centers by increasing community behavior through increasing knowledge, attitudes and behavior such as counseling and outreach. Meanwhile, for the community through the Community Health Centers, a community movement group for TB case finding and anti-TB campaigns should be formed. Keywords: Behavior, Environmental, Physical,Tuberculosis. ABSTRAK Latar Belakang: Tuberkolosis paru merupakan penyakit infeksi menular yang disebabkan oleh Mycobacterium tuberculosis dan masih menjadi masalah kesehatan dunia, termasuk Indonesia dan Indonesia menduduki urutan ketiga terbesar setelah India dan Cina.Berbagai faktor-faktor risiko yang menyebabkan penyakit tuberkulosis paru adalah faktor umur, jenis kelamin, tingkat pendidikan, pekerjaan, kebiasaan merokok, kepadatan hunian kamar tidur, pencahayaan, ventilasi, kondisi rumah, kelembaban udara, status gizi, keadaan social ekonomi dan perilaku, yang besar peranannya adalah faktor lingkungan.Tujuan: Tujuan penelitian ini adalah mengetahui Hubungan Perilaku Masyarakat Dengan Kejadian Penyakit Tuberkulosis Paru di Wilayah Kerja Puskesmas Rawat Inap Sukaraja Kecamatan Bumi Waras Kota Bandar Lampung Tahun 2022.Metode: Jenis penelitian ini termasuk penelitian analitik dengan desain kasus kontrol. Populasi kasus penelitian ini adalah penderita penyakit Tuberkulosis Paru yang tercatat pada rekam medis di Puskesmas Rawat Inap Sukaraja sebanyak 119 orang sedangkan populasi kontrol dalam penelitian ini adalah bukan penderita Tuberkulosis Paru yang bertempat tinggal di wilayah kerja Puskesmas Rawat Inap Sukaraja. Sampel kasus pada penelitian ini sebanyak 47 orang yang tercatat dalam laporan kasus Tuberkulosis di wilayah kerja Puskesmas Rawat Inap Sukaaja dan sampel kontrol pada penelitian ini adalah 47 orang atau masyarakat yang tidak tercatat menderita atau pernah menderita Tuberkulosis Paru yang bertempat tinggal di wilayah kerja Puskesmas Rawat Inap Sukaraja.Hasil: Hasil analisis bivariat menunjukkan bahwa nilai p = 0,123 >α = 0,05 maka tidak terdapat hubungan pengetahuan dengan kejadian Tuberkulosis Paru di wilayah kerja Puskesmas Rawat Inap Sukaraja tahun 2022,, nilai p = 0,023<α = 0,05 maka terdapat hubungan sikap dengan kejadian Tuberkulosis Paru di wilayah kerja Pusekesmas Rawat Inap Sukaraja tahun 2022 dan nilai p = 0,023 <α = 0,05, maka terdapat hubungan tindakan dengan kejadian Tubekulosis Paru di wilayah kerja Puskesmas Rawat Inap Sukaraja tahun 2022.Kesimpulan: Pada penelitian selanjutnya dalam menentukan hubungan factor dengan kejadian Tuberkulosis Paru lebih sfesifik perlu dilakukan penelitian lebih lanjut dengan design metode yang lebih baik lagi.Saran : bagi Puskesmas dengan peningkatan perilaku masyarakat melalui peningkatan pengetahuan, sikap dan perilaku seperti penyuluhan dan sosialisasi. Sedangkan bagi masyarakat melalui Puskesmas agar dibentuk kelompok gerakan masyarakat penemuan kasus TBC dan kampanye-kampanye anti TBC. Kata Kunci: Fisik, Lingkungan, Perilaku, Tuberkulosis.